Low-molecular heparins in thrombolytic therapy of myocardial infarction patients - I. S. Yavelov (Кардиоваскулярная терапия и профилактика, 2009)
Currently, parenteral anticoagulant therapy is considered a standard addition to thrombolytic treatment (TLT) in myocardial infarction (MI). This review analyses the results of the clinical trials demonstrating the benefits of subcutaneous low-molecular heparin enoxaparin therapy (one week before 48-hour intravenous infusion of unfractionated heparin). This evidence influenced the modern views on optimal heparin therapy in TLT-based coronary revascularisation.